Dynamic trapping and releasing photonics beyond delay-bandwidth limit in cascaded photonic crystal nanocavities - Zhe-Ming Xu; Chao Li; Jun-Fang Wu (New Journal of Physics, 2020)
Controlling the flow of light on-chip is of great importance for quantum computing and optical signal processing. In this paper, we present a theoretical study to reveal the underlying physics of how to effectively trap, store and release a signal pulse, and eventually break the delay-bandwidth limit, based on controllable EIT-like effect in dynamically tuned standing-wave cascaded nanocavities. Using this mechanism, we design a compact silicon photonic crystal system with long storing time and a delay-bandwidth product over 460, which is about two orders of magnitude greater than the reported results obtained by other methods based on static resonator system, and the trapped signal pulse can be released on demand.